Jazz dance: memórias e histórias negras do Brasil - Santos, Susan Maria da Graça Castro dos (2023)
This dissertation addresses the presence of black bodies in Jazz Dance in Brazil through the lens of the Anthropology of Ethnic-Racial Relations and dance. I intend to articulate my autoethnography in dialogue with Edson Santos and Israel Plínio, who participated in the Cia de Dança Race of Roseli Rodrigues (SP), as well as Vera Passos, who was a member of the Ballet Folclórico da Bahia in Salvador. From the presented scenarios, one can perceive how black trajectories are continually made invisible by the dominant narrative voices of white researchers and/or artists. To combat this, my main goal is to investigate, analyze, and highlight black jazz stories and memories, including mine, to point out aesthetic, poetic and afro-oriented paths in creative practices in dance.